The Rights of Man and the Care of the Self. (August 2016) - Lefebvre, Alexandre
In this article, I claim that Mary Wollstonecraft and Edmund Burke both conceive of the rights of man as a medium for individuals to care for and cultivate the self. Beginning with Michel Foucault's doubts that a concern with the care of the self can be found in modern political thought, I turn to Wollstonecraft and Burke in order to show that their debate turns precisely on the question of whether the rights of man enables or disables a care of the self. For Wollstonecraft, on the one hand, the rights of man provide women with a means to overcome a destructive set of virtues—such as beauty, chastity, and modesty—that leave them spiritually destitute and deeply unhappy. For Burke, on the other hand, such rights devastate the system of manners that had previously nurtured the self's relation to itself. Regardless of this disagreement, my key claim is that both thinkers conceive of the rights of man not just as a juridical construction but also as a comprehensive way of life. In this way, I extend Foucault's notion of the care of the self—along with his conception of ethics, conversion, and personal cultivation—to a foundational debate in the human rights tradition.